Entrepreneurial Orientation in Transport and Logistics Sector in the Last Decade: A Systematic Review - Musa, Mohammed Rabiu; Yusuf, Kabiru Musa; Elatikpo , Idris Safiyanu (Sinergi International Journal of Logistics, 2025)
This study provides a systematic quantitative assessment technique (SQAT) of entrepreneurial orientation (EO) research conducted between 2012 and 2021, focusing on the transport and logistics sector. This review aims to map and evaluate global Entrepreneurial Orientation (EO) research trends within the transport and logistics sector published between 2012 and 2021. A total of 100 EO-related publications from 34 countries were reviewed, with the majority published in 2019, by European scholars. Among all contributing nations, the United States recorded the highest number of EO publications. Most of the reviewed studies employed empirical approaches, while a smaller proportion were conceptual in nature. Four primary data collection methods were identified (surveys, secondary data, interviews, and observations), with surveys emerging as the most dominant technique. The review further revealed three major thematic areas: EO magnitude, EO consequences, and EO mechanisms, with the magnitude dimension receiving the greatest scholarly attention. The authors highlight the need for increased EO research in underrepresented regions such as South America and Australasia and advocate for more conceptual contributions to balance the dominance of empirical works. They also recommend the adoption of qualitative and mixed-method approaches to generate deeper insights, the use of qualitative and mixed-method approaches is recommended because they provide deeper insights and a more comprehensive understanding of the research problem. These methods combine numerical data with participants’ experiences and perspectives, ensuring richer, more reliable, and contextually meaningful findings. particularly within studies focusing on EO consequences and mechanisms.